Effect of the reinforcement patterns on the seismic performance of the short shear walls at Nuclear Power stations - Mohammad Ghanizadeh; Abdolreza Sarvghad Moghadam; Masood Farzam (مجله مدل سازی در مهندسی, 2016)
As the need for seismic designing of the earthquake resistant structures increases, numerous laboratory and numerical studies are being done to estimate the nonlinear response of these structures. With respect to the height to width ratio, the concrete shear walls are divided into two categories of cantilever and short shear walls. Cantilever shear walls with the aspect ratio greater than 2 demonstrate flexural behavior while short shear walls with the aspect ratio smaller than to 2 exhibit shear behavior. In this study the behavior of short reinforced concrete shear walls are investigated using the nonlinear finite element software ATENA 3D. The failure mode and the ultimate and residual shear resistance of the short shear walls, as well as the affecting parameters such as concentration of longitudinal and transverse bars at the edges of the wall, change of the horizontal and vertical bars spacing and the use of diagonal bars are studied. It is revealed that unlike the cantilever walls, the concentration of the bars at the edges have no influence on the increasing of ductility.